2021
DOI: 10.48550/arxiv.2106.10882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Affect-driven Ordinal Engagement Measurement from Video

Abstract: In education and intervention programs, person's engagement has been identified as a major factor in successful program completion. Automatic measurement of person's engagement provides useful information for instructors to meet program objectives and individualize program delivery. In this paper, we present a novel approach for video-based engagement measurement in virtual learning programs. We propose to use affect states, continuous values of valence and arousal extracted from consecutive video frames, alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Table 2 shows that some of the previous methods use conventional computer-vision features such as box filters, Gabor [18], LBP-TOP [25], and C3D [26]. In some other methods, [23,37], a CNN with convolutional layers followed by fully-connected layers is trained on a facial expression recognition dataset to extract facial embedding features. In most of the previous methods, facial Action Units (AUs), eye movement, gaze direction, and head pose features are extracted using Open-Face [40], or body pose features are extracted using OpenPose [41].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 2 shows that some of the previous methods use conventional computer-vision features such as box filters, Gabor [18], LBP-TOP [25], and C3D [26]. In some other methods, [23,37], a CNN with convolutional layers followed by fully-connected layers is trained on a facial expression recognition dataset to extract facial embedding features. In most of the previous methods, facial Action Units (AUs), eye movement, gaze direction, and head pose features are extracted using Open-Face [40], or body pose features are extracted using OpenPose [41].…”
Section: Related Workmentioning
confidence: 99%
“…Various affect and behavioral features are extracted from the video segments [37,38]. Abedi and Khan [37] showed that sequences of continuous values of valence and arousal extracted from consecutive video frames are important indicators of affective engagement.…”
Section: Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experimental work, we first analyze the importance of feature sets to select the best set of features for the resulting trained ED-MTT system. Then, we compare the performance of ED-MTT with 9 different works [1,5,15,20,24,25,27,31,32] from the state-of-the-art which will be reviewed in the next section. Our results show that ED-MTT outperforms these state-of-the-art methods with at least 6% improvement on MSE.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Engagement estimation (EE) is kind of affective computing and behavior recognition, and it goes further to probe the inner intention behind the apparent behavior and emotion. Many methods have been developed to estimate engagement in various scenarios such as general HRI, [7][8][9][10] museum tour guide, 11 classroom or distance learning, [12][13][14][15][16][17][18] and healthcare. 5,[19][20][21] Conventional approaches use nonverbal cues such as proxemics, body pose, gaze patterns, facial expressions, and context information to build classifiers.…”
Section: Introductionmentioning
confidence: 99%